2012
DOI: 10.1111/j.1755-3768.2012.02574.x
|View full text |Cite
|
Sign up to set email alerts
|

Refractive change after vitrectomy for epiretinal membrane in pseudophakic eyes

Abstract: ABSTRACT.Purpose: To report the change in refraction in pseudophakic eyes following 23-gauge vitrectomy for epiretinal membrane (ERM), without use of silicone oil, intraocular gas or scleral buckling. Methods: Retrospective review of the records of 28 pseudophakic eyes in 28 patients undergoing 23-gauge pars plana vitrectomy for ERM. All 28 eyes had a measured preoperative refraction in their records and were seen minimum 2 months after vitrectomy for measuring their refraction. Fellow eyes (28 eyes) were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Hamoudi et al reported that removal of vitreous gel itself played a role in the myopic change after vitrectomy without fluid gas exchange. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Hamoudi et al reported that removal of vitreous gel itself played a role in the myopic change after vitrectomy without fluid gas exchange. 22 …”
Section: Discussionmentioning
confidence: 99%
“…In this study, myopic shift caused by vitrectomy itself is not discussed. It is reported that pars plana vitrectomy alone also raises myopic shift by 0.2 D 11,12. Although this case may also be affected, the main reason for the refractive error is likely to be axial length estimation error.…”
Section: Discussionmentioning
confidence: 70%
“…No signi cant myopic shift was observed in our study when SE after lensectomy was compared with SE after PPV, even when comparing eyes with or without sutured sclerotomies, thus explaining why no refractive adjustment after vitrectomy was required. In a similar study of 28 pseudophakic eyes with a monofocal IOL, Hamoudi and Kofod in 2013 observed a clearly signi cant myopic shift after PPV, although the follow-up period was 8.5 months [25]. In another review article, Hamoudi and La Cour reported different shifts in SE, even though other conditions and techniques were included [26].…”
Section: Discussionmentioning
confidence: 99%